Co-infections and transmission networks of HCV, HIV-1 and HPgV among people who inject drugs - Ng, K.T.; Takebe, Y.; Chook, J.B.; Chow, W.Z.; Chan, Kok Gan; Al-Darraji, H.A.; Kamarulzaman, Adeeba; Tee, Kok Keng (Nature Publishing Group, 2015)
Co-infections with human immunodeficiency virus type 1 (HIV-1) and human pegivirus (HPgV) are common in hepatitis C virus (HCV)-infected individuals. However, analysis on the evolutionary dynamics and transmission network profiles of these viruses among individuals with multiple infections remains limited. A total of 228 injecting drug users (IDUs), either HCV-and/or HIV-1-infected, were recruited in Kuala Lumpur, Malaysia. HCV, HIV-1 and HPgV genes were sequenced, with epidemic growth rates assessed by the Bayesian coalescent method. Based on the sequence data, mono-, dual-and triple-infection were detected in 38.8%, 40.6% and 20.6% of the subjects, respectively. Fifteen transmission networks involving HCV (subtype 1a, 1b, 3a and 3b), HIV-1 (CRF33-01B) and HPgV (genotype 2) were identified and characterized. Genealogical estimates indicated that the predominant HCV, HIV-1 and HPgV genotypes were introduced into the IDUs population through multiple sub-epidemics that emerged as early as 1950s (HCV), 1980s (HIV-1) and 1990s (HPgV). By determining the difference in divergence times between viral lineages (δtMRCA), we also showed that the frequency of viral co-transmission is low among these IDUs. Despite increased access to therapy and other harm reduction interventions, the continuous emergence and coexistence of new transmission networks suggest persistent multiple viral transmissions among IDUs.